Effect of annealing on the structure and dielectric properties in PZT-PCoN ceramics - Vittayakorn N. (2014)
The solid solution between the normal ferroelectric Pb(Zr 1/2Ti1/2)O3 (PZT) and relaxor ferroelectric Pb(Co1/3Nb2/3)O3 (PCoN) was synthesized by the solid state reaction method. Sintered PZT-PCoN ceramics were annealed at temperatures ranging from 850 to 1, 100°C for 4 h. X-ray diffraction patterns revealed changes of crystalline structure after annealing, which could be correlated to the accompanied changes in dielectric properties. Furthermore, significant improvements in the dielectric responses were observed in this system. After annealing, a huge increase of up to 200% occurred in the dielectric constants, especially near the temperature of maximum dielectric constant. © 2008 Trans Tech Publications, Switzerland.